PERSEPSI MAHASISWA ATAS PROFESI AKUNTAN PUBLIK DENGAN MINAT BERKARIR DI KAP BIG 4, KANTOR AKUNTAN PUBLIK, DAN BIDANG AUDIT (STUDI PADA MAHASISWA AKUNTANSI DI DUA PERGURUAN TINGGI SWASTA) - Dessy Ariyani; Deliza Henny (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2015)
The purpose of this study is to analyze the impact of perception of public accounting perception profession, including accounting on accounting students interest for pursuing career in the field of auditing. Sample for this study consist of 150 respondent from two university in Jakarta, Trisakti University and Tarumanegara University. Multiple regression technique was used for hypotheses testing. The results of the study showed that the accounting scandals did not have a significant influence with the interest of students to work in the big 4 public accounting firm, a career in 4 public accounting firm, and a career in Auditing field . This happens because they assume that the accounting scandals just as perception only and not be able to reference the background of their future careers. However, that has a significant influence with the interest of students to work in Big 4 public accounting firm , a career in public accounting firm and a career in the field of audit is students' perceptions about the accounting profession because they believe that work or a career in the Big 4 public accounting firm, public accounting firm, and the field audit is good for beginning of career path where they want jobs that correspond to their abilities and skills, and be able to gain an advantage in career, financial and other needs. whereas the perception of Big 4 public accounting firm only has a significant influence with the interest of students for pursuing career in public accounting firm where the higher of student perception of Big 4 public accounting firm they will be increasing the interest of accounting student for pursuing carrer in public accounting firm.